2017
DOI: 10.1128/aac.00140-17
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Shows that both 14-Day Hybrid and Bismuth Quadruple Therapies Cure Most Patients with Helicobacter pylori Infection in Populations with Moderate Antibiotic Resistance

Abstract: Hybrid therapy is a novel two-step treatment achieving a high eradication rate for infection. Currently, whether this new therapy achieves a higher eradication rate than bismuth quadruple therapy remains an unanswered question. The aim of this prospective, randomized comparative study was to investigate the efficacies of 14-day hybrid therapy and bismuth quadruple therapy in the treatment of infection. From July 2013 to June 2015, eligible -infected subjects were randomly assigned to receive either 14-day bism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
0
33
0
2
Order By: Relevance
“…[21][22][23] Alternatively, bismuth or non-bismuth-containing quadruple therapy, high-dose PPI dual therapy, and hybrid therapy can attain >90% success as first-line H. pylori eradication regimens in both areas with high (>15%) and low (<15%) clarithromycin resistance. 5,6,22,[24][25][26] Recent studies reported the emergence of a novel potassium-competitive acid blocker (vonoprazan) that provides a stronger and longer-lasting effect on gastric acid suppression than other PPIs. 27 Vonoprazan-containing dual therapy (vonoprazan 20 mg + amoxicillin 750 mg twice per day) achieved a higher eradication rate than vonoprazan-containing triple therapy against clarithromycin-resistant strains (92.3% versus 76.2%; p = 0.048).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Alternatively, bismuth or non-bismuth-containing quadruple therapy, high-dose PPI dual therapy, and hybrid therapy can attain >90% success as first-line H. pylori eradication regimens in both areas with high (>15%) and low (<15%) clarithromycin resistance. 5,6,22,[24][25][26] Recent studies reported the emergence of a novel potassium-competitive acid blocker (vonoprazan) that provides a stronger and longer-lasting effect on gastric acid suppression than other PPIs. 27 Vonoprazan-containing dual therapy (vonoprazan 20 mg + amoxicillin 750 mg twice per day) achieved a higher eradication rate than vonoprazan-containing triple therapy against clarithromycin-resistant strains (92.3% versus 76.2%; p = 0.048).…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori ‐infected adult patients (age >20 years) with gastritis are documented by esophagogastroduodenoscopy in the Kaohsiung Veterans General Hospital. H pylori infection was confirmed by at least two positive results of rapid urease test, histology, and culture . Subjects with any of the following criteria were excluded from this trial: (1) previous eradication therapy, (2) allergy to any antibiotic of our study, (3) previous gastrectomy, (4) the coexistence of severe concomitant illness, (5) pregnancy or lactation women, (6) the use of antibiotics within the previous 8 weeks, and (7) taking proton pump inhibitor or histamine‐2 receptor antagonist within previous 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…H pylori infection was confirmed by at least two positive results of rapid urease test, histology, and culture. 20 Subjects with any of the following criteria were excluded from this trial: (1) previous eradication therapy, (2) allergy to any antibiotic of our study, (3) previous gastrectomy, (4) the coexistence of severe concomitant illness, (5) pregnancy or lactation women, (6) the use of antibiotics within the previous 8 weeks, and (7) taking proton pump inhibitor or histamine-2 receptor antagonist within previous 8 weeks. This trial was approved by the Institutional Review Board of the Kaohsiung Veterans General Hospital (VGHKS15-CT2-10).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations